2022
DOI: 10.1111/ipd.12946
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the presence of supernumerary teeth during the early mixed dentition stage using deep learning algorithms: A pilot study

Abstract: Background: Supernumerary teeth are a common anomaly and are frequently observed in paediatric patients. To prevent or minimize complications, early diagnosis and treatment is ideal in children with supernumerary teeth. Aim: This study aimed to apply convolutional neural network (CNN)-based deep learning to detect the presence of supernumerary teeth in children during the early mixed dentition stage. Design: Three CNN models, AlexNet, VGG16-TL, and InceptionV3-TL, were employed in this study. A total of 220 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…We previously compared the performance of three deep CNN models (i.e., AlexNet, VGG16, and InceptionV3) on the classification of supernumerary teeth. In this previous study, the classification of supernumerary teeth by these three deep CNN models yielded similar performance metrics 19) . AlexNet is an epoch-making deep CNN model that was published in 2012 21) .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…We previously compared the performance of three deep CNN models (i.e., AlexNet, VGG16, and InceptionV3) on the classification of supernumerary teeth. In this previous study, the classification of supernumerary teeth by these three deep CNN models yielded similar performance metrics 19) . AlexNet is an epoch-making deep CNN model that was published in 2012 21) .…”
Section: Discussionmentioning
confidence: 61%
“…When it comes to AI diagnosis, sensitivity is a crucial metric because high sensitivity means few false negatives (i.e., if a person has a negative test, they are likely to be free of the disease). However, previous studies have shown that any algorithm's performance (sensitivity) for both object detection and classification tasks for supernumerary teeth is in the 80% to low 90% range, and is not perfect for other metrics as well 19,[28][29][30] . Therefore, we presume that more stable results might be achieved by combining classification and object detection CNNs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations